Milk handling practices and consumption behavior among Borana pastoralists in southern Ethiopia - Kebede Amenu; Barbara Wieland; Barbara Szonyi; Delia Grace (BMC, 2019)
Abstract Background Safety and wholesomeness of milk intended for human consumption are influenced by various interlinked factors. However, information on what these factors are, especially in the pastoral traditional communities of Ethiopia, is largely lacking. The objective of this study is to assess the hygienic milk production, processing and consumption practices, and behaviors of Borana pastoralists. Methods The study used qualitative participatory research methods. Individual semi-structured interviews, focus group discussions, informal discussions, and observations were carried out on (1) milk handling practices, (2) perceptions of quality and safety of milk, including perceived criteria for good milk, (3) awareness of milk-borne diseases, and (4) perception towards milk boiling practices. The interviews and discussions were audio recorded, transcribed, and analyzed by identifying themes. Results Some risky behaviors related to milk handling and consumption were identified. These include unhygienic conditions in handling milk and milk products, consumption behaviors such as consuming raw milk purchased from markets, and children directly consuming milk from the udder of animals (e.g., goats). There was a very strong reluctance to boil milk before consumption mainly because of the misconception that nutrients in the milk are destroyed when milk is boiled and "boiled milk is dead". On the other hand, potential risk mitigation practices were identified such as smoking of milk containers (which may help reduce microbial growth), processing milk through fermentation, consuming milk in boiled tea, and a recent trend towards boiling milk for babies. However, the latter was not motivated by concern over microbial hazards but the belief that raw milk could form curds in children's stomach which might then suffocate them. Conclusion The findings highlight the need to promote hygienic handling practices of milk and closely engage with local communities to improve their understanding of milk safety to facilitate change in practices. Educating pastoralists on good milk production practices should be given priority. One of the ways to do this could be by strengthening the integration of milk hygiene in research and development programs as an entry point for behavioral change towards the safe handling and consumption of milk and milk products.